IMPACT OF FEED RATE ON ENERGY CONSUMPTION DURING CUTTING DRY BEECH WOOD WITH A CIRCULAR SAW - Temelkova, Anastasija; Trposki, Zoran (Faculty of forestry and wood technology, University of Zagreb, Croatia, 2023)
The feed rate during mechanical processing of wood is one of the factors that has a high impact on energy consumption. Energy consumption is an indicator of cutting resistance and depends directly proportionally, that is, inversely proportionally when the thickness of the sawdust is less than 0,1mm. At the same time, the teeth do not cut the wood, i.e. they do not create sawdust but wood dust. The friction of the teeth on the wood is increased, the temperature in the contact zone increases and the teeth blunted quickly. For this purpose, this paper investigates the dependence of the feed rate on the energy consumption of beech wood, when cutting dry wood with a circular saw, with the intention of determining the optimal cutting conditions for obtaining optimal values of energy consumption. In this research, three different feed rates were applied (U1=12mmin-1, U2=16mmin-1 and U3=20mmin-1) for a constant cutting height of 45mm in dry beech wood with humidity of W=10±1%. The measurements were made with a circular saw with a diameter of D=250mm, number of teeths Z=80 and width of the cut b=3,2mm. The number of revolutions is n=5500 min-1. Measurement data for energy consumption were taken with a clamp ampermeter. The obtained results show a pronounced significance, i.e. directly proportional dependence of the energy consumption on the feed rate
Keywords: beech wood, circular saw, the feed rate, energy consumption